Reception and Application of Information Literacy Instruction in Portuguese Academic Libraries - Sanches, Tatiana (2014)
Over the past decade, information literacy has been a challenge for academic libraries in Portugal. Lately, academic library professionals all over the country have been providing a consistent foundation for both teaching sessions and guidance for students. In this article a systematic literature review is used, in an attempt “to identify, appraise and synthesize all the empirical evidence that meets pre-specified eligibility criteria to answer a given research question” [1].The aim is therefore to carry out a review that seeks to systematize the state of knowledge about information literacy instruction, trying to answer the research question: how is literacy instruction conducted and provided in Portugal? The objective was to achieve an overview of the practices of information literacy instructional training in a south European country. The overall contribution to the field of IL is mainly a focus on the state of the art of information literacy instruction in Portugal.